1996
DOI: 10.1002/art.1780391010
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production during adjuvant‐induced and collagen‐induced arthritis

Abstract: Objective. To investigate the role of nitric oxide (NO) production and NO synthase (NOS) induction during adjuvant-induced arthritis (AIA) and collageninduced arthritis (CIA) in Dark Agouti rats.Methods. Urinary nitrate excretion and immune NOS (iNOS) messenger RNA (mRNA) expression were measured in the joint, lymph node, spleen, and liver tissues following the induction of either AIA or CIA.Results. Urinary nitrate excretion and iNOS mRNA expression increased substantially during joint inflammation in both mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…Subsequent animal studies confirmed these observations by showing that chondrocytes and synovial fibroblasts as well as extravasated neutrophils and macrophages express iNOS in chronic inflammatory joint diseases [2, 3]. In patients with joint inflammation, induction of iNOS was demonstrated in neutrophils, synovial fibroblasts, and chondrocytes [4, 5].…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Subsequent animal studies confirmed these observations by showing that chondrocytes and synovial fibroblasts as well as extravasated neutrophils and macrophages express iNOS in chronic inflammatory joint diseases [2, 3]. In patients with joint inflammation, induction of iNOS was demonstrated in neutrophils, synovial fibroblasts, and chondrocytes [4, 5].…”
Section: Introductionsupporting
confidence: 48%
“…This would be the assumption for the therapeutic use of an iNOS inhibitor, which is suggested to be sufficient in experimental arthritis by a number of studies [3, 6, 10]. One supposed mechanism is that L-NIL suppresses intra-articular NO synthesis by the synovium and the cartilage, and thus protects the joint possible inflammatory and erosive effects of prolonged, excessive local production of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen-induced arthritis in mice and adjuvant arthritis in rats are typical animal models of human chronic arthritis. The development of arthritis is accompanied by the induction of iNOS and subsequent NO production in these models (Stefanovic-Racic et al, 1994Connor et al, 1995;Cannon et al, 1996;Vermeire et al, 2000). Earlier studies in animal models have demonstrated that NO inhibitors have little curative effect after rheumatoid arthritis has developed (Stefanovic-Racic et al, 1995;Fletcher et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…NO is involved in both initiation and development of AA in rats (Oyanagui, 1994). Moreover, inhibitors of NOS have been shown to suppress arthritis in several animal models (Stefanovic-Racic et al, 1995;Cannon et al, 1996) and increased NO levels have been found in patients with RA (Ueki et al, 1996). Omata et al (1997) …”
Section: Discussionmentioning
confidence: 99%